GA3 application in grapes (Vitis vinifera L.) modulates different sets of genes at cluster emergence, full bloom, and berry stage as revealed by RNA sequence-based transcriptome analysis - Upadhyay, Anuradha; Maske, Smita; Jogaiah, Satisha; Kadoo, Narendra Y.; Gupta, Vidya S. (Functional & Integrative Genomics, 2018)
In grapes (Vitis vinifera L.), exogenous gibberellic acid (GA3) is applied at different stages of bunch development to achieve desirable bunch shape and berry size in seedless grapes used for table purpose. RNA sequence-based transcriptome analysis was used to understand the mechanism of GA3 action at cluster emergence, full bloom, and berry stage in table grape variety Thompson Seedless. At cluster emergence, rachis samples were collected at 6 and 24 h after application of GA3, whereas flower clusters and berry samples were collected at 6, 24, and 48 h after application at full bloom and 3–4 mm berry stages. Seven hundred thirty-three genes were differentially expressed in GA3-treated samples. At rachis and flower cluster stage respectively, 126 and 264 genes were found to be significantly differentially expressed within 6 h of GA3 application. The number of DEG reduced considerably at 24 h. However, at berry stage, major changes occurred even at 24 h and a number of DEGs at 6 and 24 h were 174 and 191, respectively. As compared to upregulated genes, larger numbers of genes were downregulated. Stage-specific response to the GA3 application was observed as evident from the unique set of DEGs at each stage and only a few common genes among three stages. Among the DEGs, 67 were transcription factors. Functional categorization and enrichment analysis revealed that several transcripts involved in sucrose and hexose metabolism, hormone and secondary metabolism, and abiotic and biotic stimuli were enriched in response to application of GA3. A high correlation was recorded for real-time PCR and transcriptome data for selected DEGs, thus indicating the robustness of transcriptome data obtained in this study for understanding the GA3 response at different stages of berry development in grape. Chromosomal localization of DEGs and identification of polymorphic microsatellite markers in selected genes have potential for their use in breeding for varieties with improved bunch architecture.
Keywords: Bunch architecture; GA3 response; Microsatellite markers; RNA seq; Transcription factors; Vitis vinifera

Global transcriptome analysis of grapevine ( Vitis vinifera L.) leaves under salt stress reveals differential response at early and late stages of stress in table grape cv. Thompson Seedless - Upadhyay, Anuradha; Gaonkar, Tulsi; Upadhyay, Ajay Kumar; Jogaiah, Satisha; Shinde, Manisha P.; Kadoo, Narendra; Gupta, Vidya Shrikant (Plant Physiology and Biochemistry, 2018)
Among the different abiotic stresses, salt stress has a significant effect on the growth and yield of grapevine (Vitis vinifera L.). In this study, we employed RNA sequence based transcriptome analysis to study salinity stress response in grape variety Thompson Seedless. Salt stress adversely affected the growth related and physiological parameters and the effect on physiological parameters was significant within 10 days of stress imposition. A total of 343 genes were differentially expressed in response to salt stress. Among the differentially expressed genes (DEGs) only 42 genes were common at early and late stages of stress. The gene enrichment analysis revealed that GO terms related to transcription factors were over-represented. Among the DEGs, 52 were transcription factors belonging to WRKY, EREB, MYB, NAC and bHLH families. Salt stress significantly affected several pathways like metabolic pathways, biosynthesis of secondary metabolites, membrane transport development related pathways etc. 343 DEGs were distributed on all the 19 chromosomes, however clustered regions of DEGs were present on chromosomes 2, 5, 6 and 12 suggesting probable QTLs for imparting tolerance to salt and other abiotic stresses. Real-time PCR of selected genes in control and treated samples of grafted and own root vines demonstrated that rootstock influenced expression of salt stress responsive genes. Microsatellite regions were identified in ten selected salt responsive genes and highly polymorphic markers were identified using fifteen grape genotypes. This information will be useful for the identification of key genes involved in salt stress tolerance in grape. The identified DEGs could also be useful for genome wide analysis for the identification of polymorphic markers for their subsequent use in molecular breeding for developing salt tolerant grape genotypes.

Gibberellic acid induces unique molecular responses in `thompson seedless' grapes as revealed by non-targeted metabolomics - Jadhav, Uma; Mundhe, Swapnil; Kumar, Yashwant; Jogaiah, Satisha; Upadhyay, Anuradha; Gupta, Vidya S.; Kadoo, Narendra Y. (Journal of Plant Growth Regulation, 2021)
Compact clusters and small berry size are the major problems associated with the commercialization of table grapes. The application of gibberellic acid 3 (GA(3)) has been a long-followed practice to overcome these issues. To analyze the molecular response of `Thompson Seedless' grapes to GA(3) treatment, we investigated the metabolomes of its rachises, clusters, and berries, 6 h and 24 h after the treatment. Metabolite profiling using non-targeted metabolomics approach revealed several metabolites, including arginine, proline, tyrosine, kaempferol, resveratrol, catechin, and so on as possible biomarkers of GA(3) treatment in grapes. GA(3) treatment greatly impacted the alanine, aspartate, and glutamate metabolism pathways, and the GA(3)-mediated alterations in the levels of certain plant growth regulators and primary metabolites were in accordance with important growth and developmental processes in grapes. This study highlights the effect of GA(3) on the profiles of certain polyphenols impacting the flavone and flavonol biosynthesis pathways and hence the nutritional aspect of grapes. The results of this study would be useful to develop self-elongating varieties simplifying the grape cultivation.
Keywords: Biosynthetic pathways; GA(3) response; GA(3) signaling; Sultana grapes; Untargeted metabolomics

Gibberellic acid induces unique molecular responses in ‘thompson seedless’ grapes as revealed by non-targeted metabolomics - Jadhav, Uma; Mundhe, Swapnil; Kumar, Yashwant; Jogaiah, Satisha; Upadhyay, Anuradha; Gupta, Vidya S.; Kadoo, Narendra Y. (Journal of Plant Growth Regulation, 2021)
Compact clusters and small berry size are the major problems associated with the commercialization of table grapes. The application of gibberellic acid 3 (GA3) has been a long-followed practice to overcome these issues. To analyze the molecular response of ‘Thompson Seedless’ grapes to GA3 treatment, we investigated the metabolomes of its rachises, clusters, and berries, 6 h and 24 h after the treatment. Metabolite profiling using non-targeted metabolomics approach revealed several metabolites, including arginine, proline, tyrosine, kaempferol, resveratrol, catechin, and so on as possible biomarkers of GA3 treatment in grapes. GA3 treatment greatly impacted the alanine, aspartate, and glutamate metabolism pathways, and the GA3-mediated alterations in the levels of certain plant growth regulators and primary metabolites were in accordance with important growth and developmental processes in grapes. This study highlights the effect of GA3 on the profiles of certain polyphenols impacting the flavone and flavonol biosynthesis pathways and hence the nutritional aspect of grapes. The results of this study would be useful to develop self-elongating varieties simplifying the grape cultivation.